Ưu điểm ngoại hình và khả năng cạnh tranh trên thị trường lao động - Cù Thị Xuân, Thảo (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
Previous studies in different countries have found that good-looking employees are more advantageous in employment, which might be explained by either higher productivity or discrimination. This study contributes to the empirical literature on physical appearance and its impact on the labor market competitive outcome by using survey data, in which the respondents provide information as well as assessed their appearance features by a self-esteem scale. This study also focuses on analyzing the impact of physical appearance advantages on competitiveness in the labor market including wage, job-finding time, wage raises, and promotion. The research shows that height does not affect the probability of a higher wage raise of employees for both genders, but male employees who are more weighted receive a lower wage. Women with large waistlines take longer to find work and have visible tattoos cause them to face difficulty in the promotion.
Keywords: Physical attractiveness; Wages; Job-finding time; Wage raise; Promotions